2011
DOI: 10.1111/j.1365-2095.2010.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

The pigmenting effect of different carotenoids on fancy carp (Cyprinus carpio)

Abstract: The optimal concentration of a panel of individual and combined carotenoid sources on skin pigmentation in fancy carp was investigated by nine experimental diets that were formulated and supplemented with astaxanthin at 25 mg kg−1, lutein at 25 and 50 mg kg−1, β‐carotene at 25, 50 and 75 mg kg−1, and lutein combined with β‐carotene at 25 : 25 and 50 : 50 mg kg−1, while a diet without supplemented carotenoid served as a control. The results showed that serum TC of fish fed diets containing supplemented with lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
17
1
6
Order By: Relevance
“…The astaxanthin concentration evaluated was within the margin recommended in the literature, which ranged from 36 to 80 mg/kg (Gouveia & Rema, 2005;Gouveia et al, 2003;Paripatananont et al, 1999). Lutein inclusion levels are also showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016). Lutein inclusion levels are also showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…The astaxanthin concentration evaluated was within the margin recommended in the literature, which ranged from 36 to 80 mg/kg (Gouveia & Rema, 2005;Gouveia et al, 2003;Paripatananont et al, 1999). Lutein inclusion levels are also showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016). Lutein inclusion levels are also showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…In the study of Yuangsoi et al . (), dietary 50 mg kg −1 lutein had also improved the redness of skin in fancy carp. The capability of converting lutein into astaxanthin was reported on fancy carp and goldfish (Hirao et al .…”
Section: Discussionmentioning
confidence: 86%
“…There are related studies on other fish species with variable results. Yuangsoi, Jintasataporn, Areechon and Tabthipwon () demonstrated that pigmentation response of skin redness of fancy carp fed with diets combined with lutein and β‐carotene at 25:25, 50:50 mg kg −1 and lutein 50 mg kg −1 was higher than in other treatments ( P ≤ 0.05), but they were similar to fish fed with a 25 mg kg −1 astaxanthin diet. Correspondingly, Yagiz, Kristinsson, Balaban, Welt, Raghavan and Marshall () reported that the colour ( a* value) of Atlantic salmon ( Salmo salar ) muscle was related to the content of astaxanthin in skin and muscle.…”
Section: Discussionmentioning
confidence: 97%